Self medication among hospitalized patients in selected secondary health facilities in South Western Nigeria - Fakeye, Titilayo O. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Practice of self-medication has not been evaluated in hospitalized patients especially in Nigerian hospitals. OBJECTIVES: To evaluate the practice of self-medication among hospitalized patients with an aim to unearth some of the reasons for, and perceptions of benefits of this type of behaviour in secondary health care facilities. METHODS: This study was carried out among 197 in-patients admitted in three secondary health facilities in southwestern Nigeria using structured questionnaire. Effects of variables such as age, gender and marital status on the practice of self medication were also evaluated using the Fisher’s Exact test at p<0.05 as level of significance. RESULTS: Response rate of the study was 93.8% with 174 respondents (88.3%) perceived that the medications prescribed for them were efficacious. Almost 38% of the respondents were self-medicating, with herbal medicines (29.2%) and western medicines (37%) partly due to side effects of the prescribed medicines. Thirty one (15.7%) respondents obtained medicines for self medication through relatives and friends. Prescription medicines used for self medication constituted 7.5%. Major reasons given for self medication included habit, availability and necessity. Ninety respondents (35.7%) had been informed by health care personnel about possible side effects of the medications. Ninety six respondents (48.7%) experienced side effects with the prescribed medications and was a major reason for self medication. Seventy six respondents (79.2%) who had side effects or other secondary symptoms informed healthcare personnel in the hospital while 16 (16.7%) informed relatives and friends. There was statistically significant association between age and the action taken on whom was informed (p=0.001). CONCLUSIONS: There is need for extra vigilance from health personnel directly responsible for care of hospitalized patients to look for incidences of self-medication and patient education on the negative aspects of administering undisclosed medicines to their health care givers especially while they are hospitalized.